2018
DOI: 10.22452/ajba.vol11no1.10
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Consumer Attitude towards Blogger Recommendations and its Impact on Purchase Intention

Abstract: Manuscript type: Research paper. Research aims: This study aims to fill in the literature gap by examining the relationship between various antecedent factors affecting consumer attitude towards blogger recommendations and their purchase intention. Design/ Methodology/ Approach: A total of 384 questionnaires were collected and analysed using the partial least squares (PLS) approach. Research findings: The results highlight the relationships existing between consumer attitude and the antecedent factors namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(112 reference statements)
2
17
0
Order By: Relevance
“…In the study, it was determined that the followers were affected by perceived usefulness of food influencers' recommendation and they developed positive attitudes towards the food products/services included in the influencers' content. This finding is supported by the findings obtained in the studies of Dhanesh and Duthler (2019), Schouten et al (2019), Ing and Ming (2018), Lim et al (2017) and Jargalsaikhan et al (2016). In addition, the results revealed that perceived usefulness of food influencers' recommendation had a positive effect on the intention to purchase food products/services.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the study, it was determined that the followers were affected by perceived usefulness of food influencers' recommendation and they developed positive attitudes towards the food products/services included in the influencers' content. This finding is supported by the findings obtained in the studies of Dhanesh and Duthler (2019), Schouten et al (2019), Ing and Ming (2018), Lim et al (2017) and Jargalsaikhan et al (2016). In addition, the results revealed that perceived usefulness of food influencers' recommendation had a positive effect on the intention to purchase food products/services.…”
Section: Discussionsupporting
confidence: 83%
“…The study also revealed the fact that consumers' attitudes have a partial mediating effect between perceived usefulness of food influencers' recommendation and intention to purchase food products/services. This finding is supported by the results obtained in the studies of Sokolova and Kefi (2019), Ing and Ming (2018), Nunes et al (2017) and Lim et al (2017).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the digital age, consumers often receive both positive and negative reviews of products sold online through the social media. They use these reviews to compare the benefits and risks before making purchase decisions (Ing & Ming, 2018). They are expected to form favourable attitudes when they perceive the benefits to be more than the risks.…”
Section: Underpinning Theoriesmentioning
confidence: 99%
“…Moreover, Changchit et al (2018) found evidence that customers felt that it was easy to perform purchasing transactions through the internet as it has a functional search button to help customers look for their intended product with detailed product descriptions. Phang and Ming (2018) also discovered that suggestions and feedback provided by bloggers are one of the crucial sources of information for the customers during the product information search process to help in making their online purchase decision, and such recommendations have been discovered to have a positive significant relationship with customer attitude. Thus, it is evident that customer perceived ease of use could influence customer online purchase intention.…”
Section: Factors Influencing Consumer Online Purchase Intentionmentioning
confidence: 99%